An evolutionary divergent pestivirus lacking the Npro gene systemically infects a whale species. Issue 1 (1st January 2019) - Jo, Wendy K.; van Elk, Cornelis; van de Bildt, Marco; van Run, Peter; Petry, Monique; Jesse, Sonja T.; Jung, Klaus; Ludlow, Martin; Kuiken, Thijs; Osterhaus, Albert
ABSTRACT: Pestiviruses typically infect members of the order Artiodactyla, including ruminants and pigs, although putative rat and bat pestiviruses have also been described. In the present study, we identified and characterized an evolutionary divergent pestivirus in the toothed whale species, harbour porpoise ( Phocoena phocoena ). We tentatively named the virus Phocoena pestivirus (PhoPeV). PhoPeV displays a typical pestivirus genome organization except for the unique absence of N pro, an N-terminal autoprotease that targets the innate host immune response. Evolutionary evidence indicates that PhoPeV emerged following an interspecies transmission event from an ancestral pestivirus that expressed N pro . We show that 9% ( n = 10) of stranded porpoises from the Dutch North Sea coast ( n = 112) were positive for PhoPeV and they displayed a systemic infection reminiscent of non-cytopathogenic persistent pestivirus infection. The identification of PhoPeV extends the host range of pestiviruses to cetaceans (dolphins, whales, porpoises), which are considered to have evolved from artiodactyls (even-toed ungulates). Elucidation of the pathophysiology of PhoPeV infection and N pro unique absence will add to our understanding of molecular mechanisms governing pestivirus pathogenesis.